2012
DOI: 10.21101/cejph.a3706
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Peginterferon alfa-2a and Ribavirin Combination Therapy in Treatment-naive Estonian Patients with Chronic Hepatitis C

Abstract: Aim: The aim of the study was to assess the efficacy of pegylated interferon (Peg-IFN) α-2a and ribavirin (RBV) combination therapy in treatmentnaive patients with chronic hepatitis C in Estonia. Methods: Out of 121 outpatients with chronic hepatitis C (73 males, 48 females, aged 19−63) enrolled in the study, 76 were infected with HCV genotype 1b and 45 with genotype 3a. At baseline, the viral load in 75.2% of patients was higher than 600,000 IU/mL. Histologically, 88.4% of patients had fibrosis score F0−2. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…The rate of SVR in the current study was 50%, which is consistent with our previous data [30], as well as with the results obtained from clinical trials [12][13][14][15] and from "real life" clinical settings [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…The rate of SVR in the current study was 50%, which is consistent with our previous data [30], as well as with the results obtained from clinical trials [12][13][14][15] and from "real life" clinical settings [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…The EHIF will cover HCV treatment for persons who are insured by the fund, yet current national HCV treatment guidelines consider injection drug use as a contraindication for HCV treatment, and do not specify any period of abstinence to qualify for treatment. (Margus, Salupere, & Ott, 2010; World Health Organization, 2013) Nevertheless, 12 % (Tuuling, 2011) to 28% (Brjalin, et al, 2012) of people in HCV treatment attribute their HCV infection to past injection drug use.…”
Section: Estoniamentioning
confidence: 99%
“…In a research study, Vadim et al found that the SVR in Genotype 1b 1 was 46.1% (19). In another study conducted by Zeuzem et al, SVR was 50% (21).…”
Section: Resultsmentioning
confidence: 95%
“…Javier et al observed that older age is associated with a lower rate of response to treatment (18). Vadim et al also concluded that the SVR rate in patients younger than 40 years old, compared to older people, is higher (19). Zeuzem et al in their study found that, some predictive factors including age, base HCV-RNA and the duration of treatment were significantly associated with SVR; however, it has no significant relationship with gender, race, weight, source of exposure, duration of exposure, the dose of Ribavirin, Metavir and Knodell scores (21).…”
Section: Resultsmentioning
confidence: 99%